Surgical Anatomy for Facelift - Batniji, Rami K. (Facial Plastic Surgery, 2017)
Knowledge of surgical anatomy is of paramount importance during surgical dissection for facelift surgery, regardless of the type of facelift procedure performed. This article reviews the relevant surgical anatomy for facelift, including the superficial musculoaponeurotic system (SMAS), and course of the facial nerve relative to the SMAS, zygomatic arch, and mandible. Also, this article reviews the various retaining ligaments, and some types of facelift procedures recommend release of these ligaments to achieve a more effective aesthetic result.
Keywords: facial nerve; facelift surgery; fasciocutaneous ligament; superficial musculoaponeurotic system